Continuous lumbar erector spinae plane block for postoperative pain management in revision hip surgery: a case report - Kinjo,Sakura (2019)
Abstract The number of total hip arthroplasty cases performed each year continues to increase; accordingly, so does the number of revision total hip arthroplasty procedures. While our traditional method of analgesia for these patients has involved multimodal medications and a continuous lumbar plexus block, we report two cases of patients who received continuous lumbar erector spinae plane blocks. Both patients exhibited excellent pain control postoperatively and were able to discharge home on postoperative day one. This case report illustrates the possible utility of continuous erector spinae plane blocks for postoperative analgesia in the more frequently occurring revision total hip arthroplasty surgeries.